1992
DOI: 10.1002/pro.5560010703
|View full text |Cite
|
Sign up to set email alerts
|

Functional interactions of ligand cofactors with Escherichia coli transcription termination factor rho. I. Binding of ATP

Abstract: Escherichia coli transcription termination factor rho is an RNA-dependent ATPase, and ATPase activity is required for all its functions. We have characterized the binding of ATP to the physiologically relevant hexameric association state of rho in the absence of RNA and have shown that there are six ATP binding sites per rho hexamer. This stoichiometry has been verified by a number of different techniques, including ultracentrifugation, ultrafiltration, and fluorescence titration studies. We have also shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
65
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 42 publications
8
65
0
Order By: Relevance
“…In this paper and its companion (Geiselmann & von Hippel, 1992) we have shown that the rho hexamer displays functional asymmetry with respect to the binding of both substrate (ATP) and cofactor (RNA). In particular, three of the six protomers of the rho hexamer (or 6 out of 12 promoters of the rho dodecamer) bind ATP and RNA much more tightly than do the remaining sites.…”
Section: Ligand Binding Asymmetry and The Asymmetric Dimer Model For mentioning
confidence: 86%
See 2 more Smart Citations
“…In this paper and its companion (Geiselmann & von Hippel, 1992) we have shown that the rho hexamer displays functional asymmetry with respect to the binding of both substrate (ATP) and cofactor (RNA). In particular, three of the six protomers of the rho hexamer (or 6 out of 12 promoters of the rho dodecamer) bind ATP and RNA much more tightly than do the remaining sites.…”
Section: Ligand Binding Asymmetry and The Asymmetric Dimer Model For mentioning
confidence: 86%
“…We calculate a 95% confidence interval of the fit parameter, taking into account the covariance of the fit parameter with the other estimated parameters as described in Geiselmann and von Hippel (1992). Binding constants of 50 x lo6 M" or greater cannot be reliably estimated from titration experiments carried out at the rho concentrations used here.…”
Section: Curve Fittingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that Rho exists under physiological conditions as a hexamer of identical subunits (19-23), organized as a trimer of asymmetric dimers with overall D3 symmetry (24). This symmetry is reflected functionally in the presence of three strong and three weak ATP (substrate) and three strong and three weak RNA (cofactor) binding sites per Rho hexamer (25)(26)(27)(28) (37,38), and subunit interaction sites have been proposed in the C-terminal region (35). Rho monomers associate to form a hexamer with D3 symmetry under physiological conditions.…”
mentioning
confidence: 99%
“…It has been shown that Rho exists under physiological conditions as a hexamer of identical subunits (19)(20)(21)(22)(23), organized as a trimer of asymmetric dimers with overall D3 symmetry (24). This symmetry is reflected functionally in the presence of three strong and three weak ATP (substrate) and three strong and three weak RNA (cofactor) binding sites per Rho hexamer (25)(26)(27)(28) (37,38), and subunit interaction sites have been proposed in the C-terminal region (35 Six molecules of ATP can bind to the Rho hexamer; three bind with high affinity (25) and three bind 20-to 30-fold more weakly (26). Thus ATP binding creates (or induces) an asymmetry within the Rho hexamer and the smallest repeating unit of Rho can be considered to be a dimer of nonequivalent subunits in which one of the monomers allows tight binding of ATP and the other is in a low-ATP-affinity state.…”
mentioning
confidence: 99%